TEACHER'S ROLE IN DEVELOPING CHARACTER-BASED LEARNING IN ISLAMIC EDUCATION - Ernawati (CV. Fahr Publishing, 2023)
The background of this study is the importance of the teacher's role in developing character-based learning in Islamic education, which aims to form students with strong character and based on Islamic values. This study aims to identify the role of teachers in developing character-based learning and evaluate the effectiveness of practical strategies used. The research method used is a literature study, which involves collecting, analyzing and synthesizing information from various relevant written sources. The results show that teachers play a crucial role as role models, facilitators and mentors in integrating character values into learning. Practical strategies such as project-based learning and the use of technology proved effective in improving students' understanding, learning motivation and social-emotional skills. In conclusion, the active and innovative role of teachers, as well as support from schools and government, is crucial in creating a conducive learning environment for students' character development.